1980
DOI: 10.1161/01.cir.61.4.671
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of upsloping ST segments in exercise electrocardiography.

Abstract: Conventional exercise electrocardiographic criteria usually involve patterns with a horizontal or downsloping ST segment. In the present study we present criteria based on upsloping ST segments and compared these criteria with the conventional criteria. Using upsloping ST-segment criteria, the amount of ST-segment depression at 80 msec after the end of the QRS complex is used as a parameter (ST criterion E, with a depression of 100 mV, and ST criterion F, with a depression of 200 mV). In the graded exercise te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
3

Year Published

1986
1986
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(32 citation statements)
references
References 30 publications
3
26
0
3
Order By: Relevance
“…ST depressions were measured at 63 ms after J-point. Both ST depressions Ͼ0.1 mV 19,20 and horizontal or downsloping (ST slope Ͻ0.2 mV/s) ST depressions Ͼ0.1 mV 17,21 were recorded. In addition, to increase sensitivity, ST depressions Ͼ0.053 mV irrespective of slope were also recorded.…”
Section: Methodsmentioning
confidence: 99%
“…ST depressions were measured at 63 ms after J-point. Both ST depressions Ͼ0.1 mV 19,20 and horizontal or downsloping (ST slope Ͻ0.2 mV/s) ST depressions Ͼ0.1 mV 17,21 were recorded. In addition, to increase sensitivity, ST depressions Ͼ0.053 mV irrespective of slope were also recorded.…”
Section: Methodsmentioning
confidence: 99%
“…STsegment elevation has been considered significant in a minority of studies (Berman et al, 1978;Campos et al, 1983;Detry et al, 1977;McNeer et al, 1978). Slowly ascending ST depression is increasingly taken into account in EECG studies as a marker of myocardial ischemia (Berman et al, 1978;Calvert et al, 1984;Chaitman et al, 1978;Detrano et al, 1984;Goldschlager et al, 1976;Kurita et al, 1977;Raffo et cil., 1979;Rijneke et al, 1980;Santingo et al, 1982;Stuart and Ellestad, 1976;Van Telligen et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The diagnostic and prognostic value of exercise-induced slowly upsloping ST-segment depression has received considerable attention in the last few decades. 7,8,14,15,24,25 Most of these studies have been performed in symptomatic populations. Goldschlager et al 24 reported that Ͼ30% of patients with upsloping ST-segment responses Ն1.5 mm or Ն1 mm with slope less than 1 mv/s were false-positive; however, this group was more likely to have triple-vessel disease and less likely to have normal coronary arteries than those with a normal ST-segment response.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies, [1][2][3][4][5][6][7][8][9][10][11][12][13] including two from our laboratory, 1,2 have shown that a horizontal or downsloping ST-segment depression Ն1 mm in response to exercise is a powerful harbinger for future coronary events (CE), ie, angina pectoris, myocardial infarction (MI), or sudden cardiac death, in an apparently healthy population, independent of conventional risk factors. In symptomatic populations, lesser ST-segment shifts defined by horizontal depression Ͻ1 mm or slowly upsloping ST segments have also demonstrated diagnostic 14,15,16 and prognostic significance. 17 However, the prognostic utility of such lesser ST-segment shifts in asymptomatic individuals has not been systematically addressed.…”
mentioning
confidence: 99%